2017
DOI: 10.1523/eneuro.0340-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Ca2+Influx Negatively Regulates Neuronal Activity

Abstract: Maintenance of neural circuit activity requires appropriate regulation of excitatory and inhibitory synaptic transmission. Recently, glia have emerged as key partners in the modulation of neuronal excitability; however, the mechanisms by which glia regulate neuronal signaling are still being elucidated. Here, we describe an analysis of how Ca2+ signals within Drosophila astrocyte-like glia regulate excitability in the nervous system. We find that Drosophila astrocytes exhibit robust Ca2+ oscillatory activity m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 50 publications
(78 reference statements)
1
39
0
Order By: Relevance
“…Cortex glial cells exhibit spontaneous and activity‐dependent fluctuations in intracellular Ca 2+ levels which depend on the glial‐specific K + ‐dependent Na 2+ /Ca 2+ exchanger Zydeco (Melom & Littleton, ). Currently, the precise role of these oscillations is not known but possibly they affect the neighboring astrocyte‐like glial cells, whose Ca 2+ dynamics clearly influence neuronal activity (Ma, Stork, Bergles, & Freeman, ; Zhang, Ormerod, & Littleton, ). A direct connection between cortex glial cells and astrocyte‐like glial cells was also demonstrated following inhibition of the Drosophila Amyloid precursor protein homolog Appl in cortex glial cells.…”
Section: Cortex Glial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortex glial cells exhibit spontaneous and activity‐dependent fluctuations in intracellular Ca 2+ levels which depend on the glial‐specific K + ‐dependent Na 2+ /Ca 2+ exchanger Zydeco (Melom & Littleton, ). Currently, the precise role of these oscillations is not known but possibly they affect the neighboring astrocyte‐like glial cells, whose Ca 2+ dynamics clearly influence neuronal activity (Ma, Stork, Bergles, & Freeman, ; Zhang, Ormerod, & Littleton, ). A direct connection between cortex glial cells and astrocyte‐like glial cells was also demonstrated following inhibition of the Drosophila Amyloid precursor protein homolog Appl in cortex glial cells.…”
Section: Cortex Glial Cellsmentioning
confidence: 99%
“…Moreover, GAT levels are elevated in an activity dependent manner demonstrating neuron‐glia crosstalk (Muthukumar et al, ). Most likely, this is due to Ca 2+ influx into astrocyte‐like glial cells which triggers rapid endocytosis of GAT from astrocytic plasma membrane (Zhang et al, ). Ca 2+ influx might be regulated by neurotransmitter receptors which are expressed by astrocytes (Bazargani & Attwell, ).…”
Section: Neuropil Associated Glial Cellsmentioning
confidence: 99%
“…Hence, one possible mechanism by which PG Ca 2+ could alter neuronal activity is through regulation of transport across the BBB. First, PG Ca 2+ activity could modulate exocytotic/endocytotic cycling of membrane proteins within the PG layer itself, similar to its role in regulating surface levels of K + channels in cortex glia 24 and GABA transporters in astrocytelike glia 22 . Second, PG Ca 2+ may regulate transport in SPG cells via a cell non-autonomous mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that chronic Ca 2+ increase in Drosophila cortex glia predispose animals to stimulation-induced seizures 24 , while acute increases in intracellular Ca 2+ in Drosophila astrocyte-like glia drives neuronal silencing 22 . To identify glial signaling pathways that may modulate neuronal excitability, we performed a genetic screen using the pan-glial driver repo-gal4 to drive expression of RNA interference (RNAi) targeting ~850 genes encoding membrane receptors, secreted ligands, ion channels and transporters, vesicular trafficking proteins and known cellular Ca 2+ homeostasis and Ca 2+ signaling pathway components 24 .…”
Section: Genetic Screening Reveals Glial Knockdown Of Dstim Increasesmentioning
confidence: 99%
See 1 more Smart Citation